Accounting Students' Intention towards the Sustainable Auditor Profession: A Case Study at ABC College - Amrullah, Muhamad Tohir; Fauziah, Nurul; Gunardi, Latifah Kurnia Putri (IAPI, 2025)
This study aims to analyze the factors that influence the intention of accounting students to become sustainable auditors. This study uses quantitative methods with data obtained through a questionnaire survey of 25 accounting study program students at ABC Campus. This research model was tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that attitudes towards sustainability, knowledge of sustainability, and university sustainability had no significant influence on students' intention to become sustainable auditors. In addition, job prospects also have no significant effect on students' career intentions. However, knowledge about sustainability, and university sustainability have a significant influence on students' attitudes towards sustainability. This study suggests that more efforts should be made to integrate the concept of sustainability in the education curriculum and career guidance in order to increase students' motivation in this field.